Inherently Catalyzed Boudouard Reaction of Bamboo Biochar for Solid Oxide Fuel Cells with Improved Performance - An, Wenting; Sun, X.; Jiao, Yong; Wang, S.; Wang, Wei; Tade, Moses; Shao, Zongping; Li, S.; Shuang, S. (American Chemical Society, 2018)
The feasibility of direct utilization of bamboo biochar (BC) as a fuel for solid oxide fuel cells (SOFCs) is studied by comparing BC to de-ashed BC (DC) and activated BC (AC) in terms of Boudouard reactivity and the performance of the fuel cell. The CO partial pressures in the carbon dioxide temperature-programmed oxidation profiles of BC and DC are 3.18 × 10 -8 and 1.04 × 10 -8 Torr at 850 °C, respectively, which indicates that BC has superior Boudouard reactivity compared to DC. The peak power densities (PPDs) of the cells fueled with BC and DC are 121 and 73 mW cm -2 at 850 °C, respectively. The inherent metal elements in BC, mainly K of 33.88 mg g -1 and Ca of 2.06 mg g -1 , play a key role in boosting its Boudouard reactivity and the performance of the cell. In addition, the loading of artificial catalysts to BC can noticeably enhance its Boudouard reactivity and gain a higher power output of the cell fed with it. The PPD of catalyst-loaded BC achieves approximately 191 mW cm -2 at 850 °C. This study reveals that BC is a promising carbon-neutral fuel for SOFCs and provides an efficient alternative to use this renewable resource in sustainable power generation.